Effect of prewarming in the cold season on thermoregulatory responses during exercise. Issue 2 (June 1996) - Torii, M; Yamasaki, M; Sasaki, T
Abstract : OBJECTIVE: To assess whether thermoregulation in the cold season can be affected by prewarming before exercise. METHODS: Four healthy non-athletic unacclimatised males were exercised to the same degree in summer and winter on a bicycle ergometer without prewarming (experiment 1) and after prewarming by sitting for 30 min in a room at 30 degrees C (experiment 2). During exercise, sweat production and rectal and skin temperatures were measured continuously. RESULTS: There was seasonal variation in sweating capacity and sensitivity and in heat storage during exercise without prewarming (experiment 1). After the subjects were warmed before exercise, there was no such seasonal variation in their sweat rates during exercise at 30 degrees C and 40 degrees C (experiment 2). In both cases, the sweat rate and skin temperature were dependent on the environmental temperature, and the sweat rate and core temperature were dependent on the workload. In the cold season, sweating sensitivity and evaporative cooling response could be enhanced by thermal stimulation. There was no seasonal difference in the relation between evaporative heat loss and metabolic rate in the two thermal conditions. These values did not differ significantly between winter after prewarming and summer (P > 0.05), neither did heat storage and metabolic heat production at various workloads (P > 0.05). CONCLUSIONS: There is adaptation of the thermoregulatory mechanisms during temperature acclimatisation. Body warming enhances not only the heat dissipating activity of the thermoregulatory centre but also the induction of peripheral sweat gland activity. Seasonal change of sweat rate in exercising men can be eliminated through a different type of acclimatisation by prewarming in the cold season.